2012
DOI: 10.1016/j.mrgentox.2012.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the in vitro genotoxicity of methyl-pyrazole pesticides in human cells

Abstract: Consumers are exposed daily to several pesticide residues in food, which can be of potential concern for human health. Based on a previous study dealing with exposure of the French population to pesticide residues via the food, we selected 14 pesticides frequently found in foodstuffs, on the basis of their persistence in the environment or their bioaccumulation in the food chain. In a first step, the objective of this study was to investigate if the 14 selected pesticides were potentially cytotoxic and genotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…It is indicated that fenproximate tested with various test systems (Ames test, DNA repair test, chromosomal aberration test, unsheduled DNA synthesis test) has no genotoxic potential in studies performed on living systems, including procaryotic and eucaryotic organisms (EFSA, 2010). Graillot et al (2012) demonstrated that bixapen was genotoxic in jurkat cells with the same genotoxic potential as observed in SH-SY%Y cells. Huang et al (2008) and Xia et al (2008) indicated that different cells can show same effects against xenobiotics, including pesticides.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It is indicated that fenproximate tested with various test systems (Ames test, DNA repair test, chromosomal aberration test, unsheduled DNA synthesis test) has no genotoxic potential in studies performed on living systems, including procaryotic and eucaryotic organisms (EFSA, 2010). Graillot et al (2012) demonstrated that bixapen was genotoxic in jurkat cells with the same genotoxic potential as observed in SH-SY%Y cells. Huang et al (2008) and Xia et al (2008) indicated that different cells can show same effects against xenobiotics, including pesticides.…”
Section: Discussionmentioning
confidence: 64%
“…Graillot et al (2012) observed an increased production of reactive oxygen species (ROS) in jurkat cells in the presence of four methylpyrazoles and demostrated that the four methylpyrazole pesticides (tebufenpyrad, bixafen, fenpyroximat, and tolfenpyrad) induced DNA damage in human cell lines. The relationship between the increase of DNA damage level in comet assay in this study and the increase in ROS level obtained in the study performed by Graillot is redolent of oxidative damage of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The H2AX In Cell Western technique was performed as previously described with the following modifications [27], [28], [29], [30], [34]. Briefly, cells were dispensed in 96-well cell culture plate (40×10 3 cells, 200 µL/well) and were treated in duplicate, 16 h later, with the model compounds or vehicle (DMSO) in serum free medium.…”
Section: Methodsmentioning
confidence: 99%
“…Raw absorbance data was averaged for the duplicate, corrected for background; the relative fluorescence units from the scanning allowed a quantitative analysis. The ICW technique allows the determination of cytotoxicity and genotoxicity in a single experiment [27], [28], [30], [34]. For determination of genotoxicity, relative fluorescent units for γH2AX per cell (as determined by γH2AX divided by DNA content) were divided by the respective controls (vehicle only), in order to determine the change in phosphorylation of H2AX levels relative to control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation